The Effect Of Investment, Work Force, And Education Level On The Real Growth Of GRDP In The Bangka Belitung Islands - Hasdiar B. Chammearc; Pudji Astuty (Journal Research of Social Science, Economics, and Management, 2023)
The study strives to determine the effect of investment, workforce, and level of education on the real GRDP growth in Bangka Belitung Province either partially or simultaneously. The research is quantitative descriptive research, and the research method used is panel data regression analysis. This study uses time series data published by BPS Bangka Belitung Islands. The results of this study show: 1) There is an effect of investment, workforce, and education level on the real GRDP growth simultaneously in the Bangka Belitung Islands Province. 2) There is an effect of investment, workforce, and education level on the real GRDP growth partially in the Bangka Belitung Islands Province. 3) Of the three research variables, namely Investment, Workforce, and Education Level, the variable that has the most dominant effect on the PDRB of the Bangka Belitung Islands is the Labor Force variable.